Longitudinal assessment of D-dimer and plasminogen activator inhibitor type-1 plasma levels in pregnant women with risk factors for preeclampsia - Flávia Campos Lucena; Eura Martins Lage; Patrícia Gonçalves Teixeira; Alexandre Simões Barbosa; Rejane Diniz; Bashir Lwaleed; André Talvani; Patrícia Nessralla Alpoim; Luiza Oliveira Perucci; Luci Maria SantAna Dusse (Taylor & Francis Group, 2019)
Objective: Investigating D-Dimer/D-Di and plasminogen activator inhibitor type-1/PAI-1 levels throughout gestation in women with preeclampsia/PE risk factors. Methods: D-Di and PAI-1 plasma levels were determined in 28 women at 12-19, 20-29, 30-34 and 35-40 weeks of gestation. Results: D-Di was lower at 12-19 weeks and higher at 30-34 weeks in women who developed PE versus who did not develop it. D-Di increased throughout gestation in both groups, peaking earlier in pregnant women who developed PE versus who did not develop it. PA1-1 increased across gestation, but it didn't differ between groups. Conclusion: D-Di was able to discriminate these groups of women at 12-19 and 30-34 weeks of gestation.